Development of Pesantren Teachers In The Perspective of Uswah Nubuwah - Supian Supian; K. A Rahman; Sulhi M Daud; Nanang Thohirin (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
Qualitative research using this case study approach is to explore and describe the supervision of the principal in managing teachers from the perspective of the nature of the Prophet: Shidiq, Amanah, Tabligh, Fathonah in the Hidayatullah Islamic Boarding School, Muara Jambi Regency. The data were collected through interviews and document studies of 4 participants, namely the headmaster of kindergarten/early childhood schools, SDIT, MTs, and the leader of the Hidayatullah Muaro Islamic Boarding School Jambi. Interview data were analyzed using a case and cross-case analysis between participants. The results showed four main categories, namely (1) like fingerprints, most of them had been carried out (2) like the mandate that they had been carried out (3) like tabligh that they had run as the program (4) there were obstacles and supporters in implementing the program following the nature of the prophet. The obstacles are laziness, not istiqomah (discipline), a busy schedule of activities, lack of awareness, while the supporting factors are a family atmosphere, halaqoh marhalah ula, marhalah wustho, deliberation, meetings, congregational prayers, reading the Koran, recitation, training, Madrasah working group (KKM), and Teacher working group (KKG).